Book Reviews. (1st March 2017) - Tomaselli, Keyan; Tchouaffe, Jean-Olivier
HARRY ALAN TOWERS: THE TRANSNATIONAL CAREER OF A CINEMATIC CONTRARIAN, DAVE MANN (ED.) (2014) Jefferson, NC: McFarland and Co., 251pp., ISBN: 9780786479825, p/bk, $38.94Directory of World Cinema: Africa, Blandine Stefanson and Sheila Petty (eds) (2015) Intellect and University of Chicago Press, Bristol, UK and Chicago, IL ISBN: 9781783203918, Paperback, 420pp., $36